Takayasu Arteritis in a Patient with Down Syndrome: A Case Report - Rodrigues, Mariana Ferreira Borges Firmo; Rodrigues, Emanuel Firmo; Rodrigues, Pâmela de Oliveira Gonçalves; Cadore, Leonardo Suhre; Medeiros, Laís Muller; Stoquero, Vanessa; Coluci, Valentina de Oliveira; Ferreira, Eduardo Melo; Mendes, Pedro Natel Kugler (Brazilian Journal of Case Reports, 2026)
Takayasu arteritis is a chronic vasculitis of large- and medium-sized vessels that primarily involves the aorta and its proximal branches. It is an uncommon disease that occurs predominantly in young women. Histopathologically, the affected vessels are characterized by mononuclear infiltrate and granulomatous inflammation of the tunica media, leading to arterial wall thickening, with stenosis, occlusion, and aneurysmal dilation. The present article aims to report on a case of Takayasu arteritis in a patient with Down syndrome.